Standardization and validation of a conventional high yield platelet-rich plasma preparation protocol. (October 2022) - Muthu, Sathish; Krishnan, Anand; Ramanathan, Karthik Raja
Abstract: Background: Of late, numerous randomised controlled trials report platelet-rich plasma (PRP) to be ineffective with preparation protocols of low platelet yield despite using expensive commercial PRP kits. Objective: This study aims to identify and standardize a preparation protocol for PRP with maximum platelets yield and concentration to obtain favourable results without the use of commercial preparation kits. Materials & methods: Blood samples were collected from 40 healthy volunteers who signed informed consent for participation in the study. The double spin protocol of PRP preparation was analyzed for variables such as centrifugal acceleration, time, and volume of blood processed and final product utilized. The final PRP prepared was investigated for platelet recovery, concentration, integrity, and viability. Each protocol investigated with technical and biological duplicates to avoid reporting and sampling bias. Results: We noted maximum platelet recovery (86–99%) with a consistent 6.4 ± 0.8 times the baseline concentration of platelets with first centrifugation at 100 g for 15 min followed by second centrifugation at 1600 g for 20 min. We did not note a loss of integrity or viability of the platelets in the final product from the above-said protocol. We also validated the protocol among all the study participants demonstrating consistency. Conclusion: The preparation of PRP by the double-spin protocol using 10 ml of blood at 100 g followed by 1600 g for 15 and 20 min respectively in a 15 ml tube and using the lower 1/3rd of the final product demonstrated consistent high platelet recovery (86–99%) and concentration (6x) without disturbing the platelet integrity or viability. Highlights: Standardized protocol is necessary for comparable results across studies using PRP. The preparation of PRP by the double-spin protocol is recommended. Double-spin protocol at 100 g followed by 1600 g for 15 and 20 min is validated. Lower 1/3rd of the final product demonstrated high platelet recovery (86–99%). Consistent concentration (6x) is obtained without disturbing the platelet viability.